Implementasi Pendidikan Karakter pada Pembelajaran Jarak Jauh di Era Pandemi Covid-19 di Sekolah Dasar - Maman Surahman; Siska Mega Diana; Dayu Rika Perdana (JURNAL INOVATIF ILMU PENDIDIKAN, 2021)
Distance Learning (Pembelajaran Jarak Jauh/PJJ) is a transition to face-to-face teaching and learning activities in a school setting, in which due to the COVID-19 pandemic education is experiencing challenges, especially in formal education and school activities must be conducted offline and online. Currently, distance learning is determining key to continuing education. Regardless of the circumstance and condition of each student, they must be provided with an optimal education. Hence, nowadays, it is important to instill and maintain character in students that in any circumstances, education is an absolute term. The purpose of this study was to investigate the implementation of character education in distance learning amid the COVID-19 pandemic in elementary school. This research used a qualitative descriptive. The results of character education research can develop life skills or student skills in the learning process, in this case how students can be responsible for each assignment, as well as discipline in participating in distance learning.Keywords: Character Education, Distance Learning, Amid COVID-19DOI: http://dx.doi.org/10.23960/jiip.v3i2.23279